Reflections about the theoretical-methodological sesgos presented in studies with a gender perspective referred to women (Dissertare, 2017)
With the present article, we intend to socialize a set of reflections, derived from the critical analysis on the theoretical-methodological biases in the studies of women from the gender perspective. This material is part of the result of a research process that culminated with a master's thesis, which is part of the documentary research modality, with a bibliographic design. For the purposes of this study, the analytical-synthetic method is applied, as provided by Eyssautier, Hurtado y Toro and Cerda García, which allows the decomposition of the texts into their simplest elements, analyzing each of them separately, to then group the parts, enrich and consider them as a whole. The results of the study reflect that the theoretical-methodological biases in the studies of women from a gender perspective are manifested through the following elements: androcentrism, sexism, ethnocentrism, poor socialization of results, universality, women as object of the investigation, among others. As a final reflection, a series of challenges are posed by committing research with a gender perspective in the future as the imperative to assume that research from this perspective requires internalization and commitment to a series of principles, values and goals that are distinctive of this way of doing research.
Keywords: Gender; theoretical-methodological sesgos; studies referred to women